Improvement from mustard-Boro-T. Aman cropping pattern to mustard-Boro-jute-T. Aman - Rahman, MM; Rahaman, MA; Ahmed, M; Uddin, MM; Choudhury, AK (Bangladesh Journal of Agricultural Research, 2015)
The experiment was conducted at the farmers field of FSRD site, Elenga and MLT site Modhupur, Tangail during two consecutive years 2011-12 and 2012- 13 to study the productivity, production efficiency, land use efficiency and economic return of the improved cropping pattern (Mustard - Boro - Jute -T. Aman) against the existing cropping pattern (Mustard -Boro - T. Aman) through incorporating of modern crop varieties and improved management practices. The experiment was laid out in randomized complete block design with six dispersed replications. The pooled data of improved management practice for the pattern produced significantly higher yield in Mustard and T. Aman rice respectively and also gave additional jute yield. The gross return and gross margin were higher in improved pattern compared to that of existing farmers pattern with only 149 and 151% extra cost at FSRD site, Elenga and MLT site Modhupur, respectively. The higher benefit cost ratio (1.74 and 1.79), rice equivalent yield (22.41 and 21.82), production efficiency (40.19 and 39.48) and land-use efficiency (95.75 and 96.48) indicated the superiority of the improved pattern over the farmers existing pattern at both sites. Higher rice equivalent yield indicates that improved cropping pattern (Mustard - Boro - Jute -T. Aman) could be suitable in Tangail region for increasing crop productivity as well as cropping intensity. Bangladesh J. Agril. Res. 40(2): 259-270 June 2015